2020
DOI: 10.1111/ppl.13086
|View full text |Cite
|
Sign up to set email alerts
|

Blue light induces major changes in the gene expression profile of the cyanobacterium Synechocystis sp. PCC 6803

Abstract: Although cyanobacteria absorb blue light, they use it less efficiently for photosynthesis than other colors absorbed by their photosynthetic pigments. A plausible explanation for this enigmatic phenomenon is that blue light is not absorbed by phycobilisomes and, hence, causes an excitation shortage at photosystem II (PSII). This hypothesis is supported by recent physiological studies, but a comprehensive understanding of the underlying changes in gene expression is still lacking. In this study, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 97 publications
3
28
1
Order By: Relevance
“…It is a question, whether the special redistribution of PSI at L-D cycle is favorable for larger NADPH production (formed in photosynthesis) that is preferentially used (more than NADH) as a reductant source for ROS detoxification (Flores and Herrero, 2005). The similar light-induced response on PSI level is visible also for cyanobacterial cells acclimated to highlight (Kopečná et al, 2012) or to a light of different quality (El Bissati and Kirilovsky, 2001;Luimstra et al, 2020). It is well know that a shift from low-light to high-light growth conditions stimulates decrease in the PSI to PSII ratio due to selective suppression of the amount of functional PSI (Murakami and Fujita, 1993;Murakami et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a question, whether the special redistribution of PSI at L-D cycle is favorable for larger NADPH production (formed in photosynthesis) that is preferentially used (more than NADH) as a reductant source for ROS detoxification (Flores and Herrero, 2005). The similar light-induced response on PSI level is visible also for cyanobacterial cells acclimated to highlight (Kopečná et al, 2012) or to a light of different quality (El Bissati and Kirilovsky, 2001;Luimstra et al, 2020). It is well know that a shift from low-light to high-light growth conditions stimulates decrease in the PSI to PSII ratio due to selective suppression of the amount of functional PSI (Murakami and Fujita, 1993;Murakami et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In light with the above-mentioned results, we tend to suggest that also TM plasticity, as we saw it based on PSI/PSII and PBS co-localization ( Figure 2 ), is controlled by PSI to PSII ratio. The change in the ratio is induced by light and includes regulation of several genes ( Luimstra et al, 2020 ). However, it is still not clear whether PSI to PSII ratio is a redox-control ( El Bissati and Kirilovsky, 2001 ) or a photoreceptor control process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, photosynthesis in cyanobacteria can be negatively influenced by blue light. Luimstra et al (2018Luimstra et al ( , 2020 showed that there is a major imbalance in electron transport between photo system (PS)I and PSII in the cyanobacterial genus Synechocystis. Cyanobacteria have more chlorophyll in PSI than in PSII.…”
Section: Drastic Shift In Natural Phytoplankton Communitiesmentioning
confidence: 99%
“…Complementary to chlorophyll-a, cyanobacteria have accessory pigments (phycobilins) allowing them efficiently to use light within the green gap of chlorophyll-a and -b (Britton, 1983). Luimstra et al (2020) showed in their laboratory study that cyanobacteria growth under blue light decreases because of low photosynthetic efficiency, when phycobilins are present.…”
Section: Introductionmentioning
confidence: 99%
“…Light intensity is positively correlated with both the number of β-carboxysomes per cell and the carbon fixation capacity [ 120 ], and is essential for maximising biomass accumulation [ 121 123 ]. However, cyanobacteria are known to experience light-induced stress dependent on the light intensity [ 121 ] and wavelength [ 124 ]. A common mechanism of adaptation to changes in light intensity is the alteration of flux between the synthesis and use of glycogen and other carbon sinks [ 125 ].…”
Section: Environmental Stressmentioning
confidence: 99%